THE EFFECT OF ORGANIZATIONAL ENVIRONMENT AND DISCIPLINE ON EMPLOYEE PERFORMANCE - Permata Sari, Adella; Budi Rahayu; Desi Kristanti (Program Studi Ekonomi Syariah, Institut Agama Islam Pangeran Diponegoro Nganjuk, 2025)
This study aims to determine the Work Environment and Work Discipline on Employee Performance at The Farrel Nganjuk Hotel. The study uses a quantitative approach with a multiple linear regression analysis method used to test the hypothesis after going through validity, reliability, and classical assumption tests. Data were obtained by distributing questionnaires to 32 respondents using saturated sampling techniques. The results of the study indicate that the Work Environment and Work Discipline have a positive and significant effect on employee performance. A conducive work environment and high discipline can increase employee productivity and performance as a whole